3D CFD analysis of the performance of oblique and composite side weirs in converging channels. Issue 4 (4th July 2021) - Maranzoni, Andrea; Tomirotti, Massimo
Abstract : Conventional rectangular side weirs installed along prismatic open-channels may have low efficiency. One practical way to overcome this problem may be to insert the weir in the oblique side of a converging channel. In this paper, the performance of oblique straight side weirs or two-segment single-cranked side weirs inserted in rectangular converging channels are analysed through 3D computational fluid dynamics (CFD) for subcritical steady flow conditions. The numerical simulations were performed through a widely available software package by applying the VOF method to the Reynolds-averaged Navier–Stokes equations and adopting the Reynolds stress model for turbulence closure. The model is validated against experimental data previously obtained by the authors. The results provide insight into the features of the flow field and show the effect of the channel contraction rate on diversion efficiency. As regards the two-segment single-cranked weir, the "concave" arrangement has been verified as being more efficient than the "convex" one.